Optimizing beam-ion confinement in ITER by adjusting the toroidal phase of the 3D magnetic fields applied for ELM control. (5th March 2021) - Sanchis, L.; Garcia-Munoz, M.; Viezzer, E.; Loarte, A.; Li, L.; Liu, Y.Q.; Snicker, A.; Chen, L.; Zonca, F.; Pinches, S.D.; Zarzoso, D.
Abstract: The confinement of neutral beam injection (NBI) particles in the presence of n = 3 resonant magnetic perturbations (RMPs) in 15 MA ITER DT plasmas has been studied using full orbit ASCOT simulations. Realistic NBI distribution functions, and 3D wall and equilibria, including the plasma response to the externally applied 3D fields calculated with MARS-F, have been employed. The observed total fast-ion losses depend on the poloidal spectra of the applied n = 3 RMP as well as on the absolute toroidal phase of the applied perturbation with respect to the NBI birth distribution. The absolute toroidal phase of the RMP perturbation does not affect the ELM control capabilities, which makes it a key parameter in the confinement optimization. The physics mechanisms underlying the observed fast-ion losses induced by the applied 3D fields have been studied in terms of the variation of the particle canonical angular momentum ( δP ϕ ) induced by the applied 3D fields. The presented simulations indicate that the transport is located in an edge resonant transport layer as observed previously in ASDEX upgrade studies. Similarly, our results indicate that an overlapping of several linear and nonlinear resonances at the edge of the plasma might be responsible for the observed fast-ion losses. The results presented here may help to optimize the RMP configuration with respect to the NBI confinement in future ITER discharges.